KEDUDUKAN NOTA PEMERIKSAAN DALAM PUTUSAN PENGADILAN HUBUNGAN INDUSTRIAL: The Position of Examination Notes in Industrial Relations Court Decisions - Sugeng Santoso PN (Faculty of Law, Trisakti University, 2024)
This research discusses the position of examination notes in the decisions of industrial relations courts. Examination notes are instruments issued by labor inspectors to examine and assess the compliance of an event with the prevailing norms in industrial relations. This study examines how examination notes are recognized and treated in the process of industrial relations court proceedings, particularly in the context of evidence presentation and judicial decision-making. The research method used is juridical-normative with a statutory and case approach. The results show that examination notes are used as formal evidence in the form of documents in industrial relations court proceedings. However, despite being used as documentary evidence, examination notes have different positions in each decision because some judges consider examination notes as decisive factors in making decisions, while others disregard them and do not consider them as one of the considerations in making court decisions. This research provides valuable insights for labor law practitioners and decision-makers in dealing with cases involving examination notes in industrial relations courts.